Luis Antonio de Villena’s “Marginados”: from "malditismo" to solidarity - Quintana, Belén (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
From El viaje a Bizancio to La muerte únicamente Luis Antonio de Villena’s poetry implies eagerness for a meeting with platonic perfection as to beauty and love. After the failure of erotism and the art as a way of mistic union, he tracks selfdestruction in Marginados, Asuntos de delirio y Celebración del libertino to, finally, reject the polished platonic promises and its mistic nostalgia in favour of desolating down to earth feeling in front of wich, solidarity is the only possible answer.